A Revised Version of the Multidimensional Health Locus of Control Scales for Labour and Delivery (MHLC-LD-R) - Konkolÿ Thege, Barna; Sallay, Viola; Rafael, Beatrix; Martos, Tamás (European Journal of Mental Health, 2018)
The aim of the present study was to develop and psychometrically investigate a revised version of the Multidimensional Health Locus of Control Scales for Labour and Delivery (MHLC-LD). The rationale for this development was the need to assess labour and delivery specific health-related control beliefs regardless of the respondent-s reproductive stage or role in giving birth (e.g., woman in reproductive age but not pregnant, expectant mother, support person, spouse, health care provider). Methods: Altogether, 991 women (Mage=26.45 years, SD=5.42) completed the online survey, 767 (77.4%) of whom were pregnant. Beyond the newly developed, revised version of the Multidimensional Health Locus of Control Scales for Labour and Delivery (MHLC-LD-R), the test battery included items measuring sociodemographic characteristics, self-rated health, general health-related control beliefs, attitudes toward certain birth-related issues, and level of fulfilment with regards to autonomy and competence needs. Results: Confirmatory factor analyses supported a three-factor solution representing internal-, chance-, and health care professional-related control beliefs. The internal consistency of each 4-item subscale was good. The analyses to test construct validity supported the convergent and divergent validity of the MHLC-LD-R dimensions. Conclusion: The MHLC-LD-R is an economic and psychometrically adequate tool to assess delivery-related control beliefs regardless of the individual-s actual stage in the reproductive life cycle or role in giving birth. Further research is needed using the instrument with partners and other relevant actors in the process of labour and delivery.